Multiple biomarkers response in a Neotropical fish exposed to paralytic shellfish toxins (PSTs). (January 2020) - Calado, Sabrina Loise de Morais; Santos, Gustavo Souza; Vicentini, Maiara; Bozza, Deivyson Cattine; Prodocimo, Viviane; Magalhães, Valéria Freitas de; Cestari, Marta Margarete; Silva de Assis, Helena Cristina
Abstract: The Alagados Reservoir (Southern Brazil) is used as water supply, and since 2002 there have been reports with a presence of cyanobacterial blooms and cyanotoxins. In order to assess the water quality and the ecological integrity of the reservoir, we evaluated biochemical, genotoxic and osmoregulatory biomarkers in the freshwater cichlid fish ( Geophagus brasiliensis ) that were exposed to PSTs. The fish were sampled in the Alagados Reservoir in February 2016 (Summer) and were divided in three groups: 1) Reservoir group (RES): fish were collected immediately after sampling; 2) Depuration group (DEP): fish were submitted to the depuration experiment for 90 days in the laboratory; and 3) Reproduction group (REP): fish were kept in the laboratory until the fertilization and the chemical analyses were performed on the offspring (F1 generation). In the RES and DEP the blood, brain, muscle, liver and gills were collected for biochemical, genotoxic and osmoregulatory biomarkers analysis. Our results showed that the fish from the Alagados Reservoir (RES) presented oxidative stress and DNA damage; and after 90 days (DEP), the antioxidant system and DNA damage were recovered. Although PSTs were considered a risk to the ecological integrity of this water body; PSTs concentrations were not found in the tissues of the F1 generation. In addition, the biomarkers used were useful tools to evaluate the effects of environment contamination. Therefore, it is necessary to develop new technologies and monitoring programs in order to reduce cyanobaterial blooms, cyanotoxins and human activities that cause the contamination in aquatic environments. Highlights: Oxidative stress and DNA damage were observed in fish. Depuration in fish occurred during the 90 days. The PSTs concentrations were not found in the fish offspring. The set of biomarkers used was efficient to evaluate the fish health.